Asynchronous cooperative transmission mechanism using distributed Orthogonal Frequency Division Multiplexing for mobile ad hoc networks. (3rd July 2008) - Yu, Quan; Fu, Tielian; Zheng, Jun; Zhang, Baoxian
In this article, we propose an asynchronous cooperative transmission mechanism for Mobile ad hoc Networks (MANETs). The proposed cooperative transmission mechanism employs distributed Unitary Space-Frequency Coded-Orthogonal Frequency Division Multiplexing (USFC-OFDM), which does not require any channel estimation and has a lower decoding complexity, and therefore can provide better reliability and robustness when mobile nodes move fast. Moreover, it can achieve a larger diversity gain and multiplexing gain, and can thus combat fast time-varying and frequency-selective channel fading, and tolerate imperfect synchronisation among mobile nodes. To support USFC-OFDM, a Time Division Multiple Access-based Cooperative Medium Access Control protocol and an on-demand Cooperative Dynamic Source Routing protocol are also proposed. Through simulation results, we show that the proposed USFC-OFDM-based cooperative transmission mechanism can significantly improve the network performance in terms of packet delivery ratio and bit error rate in highly dynamic mobile environments.